Endobronchial Lipomatous Polyp: A Rare Benign Tumor of the Lung - Salim Surani; Karen Allen; Saherish Surani; Joseph Varon (Case Reports in Pulmonology)
Endobronchial lipomatous polyp is a rare nonmalignant tumor of the lung. It comprises 5% of the benign lung tumor, with the majority of benign tumors being hamartoma. Lipomatous polyp often leads to endobronchial lesion, associated with postobstructive pneumonia, hemoptysis, and atelectasis. We hereby present a case and discussion of an elderly man with endobronchial lipomatous polyp, presenting as recurrent pneumonia.